Perfil bioquímico sérico de bezerros mestiços durante o primeiro ano de vida - Moraes, Danielle Vitorino (2011)
The study of the physiological traits of calves has contributed to the helped in the explanation, recognition and differentiation of morbid states that affect these animals. Furthermore, this data is essential to ensure the clinical care of these neonates to reduce economic losses in bovine breeding. Based on the age and gender, this study is aimed to evaluate the concentrations of the serum biochemical profile of crossbred calves from birth to 360 days. 30 crossbred calves were used and 13 blood samples were taken from each at monthly intervals. The first withdraw was on the one a thre days of birth. The concentrations of total serum protein, albumin, globulin, ALP, GGT, AST, ALT, calcium, phosphorus, magnesium, calcium ionized, creatinine, urea, triglycerides and cholesterol. Blood analyses were performed by using the automated multichannel analyzer Chem Well®. All proteins, enzymes and minerals were influenced by age. Urea was the only parameter that was not statistically different according to age. We conclude that age has an influence on the values of most biochemical parameters.